When does the influence of maturation on anthropometric and physical fitness characteristics increase and subside? - Towlson, C.; Cobley, S.; Parkin, G.; Lovell, R. (Scandinavian Journal of Medicine & Science in Sports, 2018)
The relationships between maturation and anthropometric and physical performance characteristics are dynamic and often asynchronous; confounding the capability to accurately evaluate performance during adolescence. This study aimed to (i) examine the influence of chronological age (CA) and somatic maturation (YPHV) upon anthropometric and physical performance parameters, and (ii) identify the transition/change time-points in these relationships using segmental regression. N=969 soccer players (8-18 years of age) completed anthropometric and physical test assessments, including a counter-movement jump (CMJ), agility T-test, 10 and 20m sprints, and multi-stage fitness test (MSFT). When modelled against CA and YPHV, results identified time-point phases with increased rates of stature (CA - 7.5, YPHV - 8.6 cm·year-1 at 10.7-15.2 years or -3.2 to +0.8 YPHV) and body mass gain (CA - 7.1, YPHV - 7.5 kg·year-1 at 11.9-16.1 years or -1.6 to +4.0 YPHV); followed by gain reductions. Increased rates of sprint performance development (31-43% gains) occurred at 11.8-15.8 CA or -1.8 to +1.2 YPHV; with gains subsiding thereafter. CMJ, T-test, and MSFT gains appeared relatively linear with no change in developmental rate apparent. Developmental tempos did again however subside at circa (CMJ and T-Test) to post-PHV (MSFT). Based on our sample and analysis, periods of increased developmental rates (stature, mass, sprint) were apparent alongside progressive gains for other physical measures, before all subsided at particular age and maturation time-points. Findings highlight dynamic asynchronous development of players, physical attributes, and the need to account for the influence of maturation on athletic performance until post-PHV.